Kenosis: the self-emptying of Christ in scripture and theology - Nimmo, Paul T.; Johnson, Keith L. (William B. Eerdmans Publishing Company, 2022)
"An overview of the past and present significance of the theological doctrine of kenosis-the claim in the "Christ-hymn" of Philippians 2 that Jesus emptied and humbled himself in obedience on his way to death upon the cross"--